Implementasi Qawa’id Al-Fiqh Pada Prinsip-Prinsip Ekonomi Syariah - Achmad Fageh (JES (Jurnal Ekonomi Syariah), 2017)
To assess and find a sharia law on contemporary issues, including economic activity, it is absolutely required ushul fiqh. Supposing, ushul fiqh is the production process to produce a product of jurisprudence by means of operational standards qawa'id fiqhiyyah. A law of fiqih can not be removed from the proposition/source (the text of the al-Quran and Hadith) without going through the ushul fiqh and qawa'id fiqhiyyah. Not all qawa'id fiqhiyyah can accommodate interests in activities mu'amalah instead. Only a few of qawa'id is associated with transactions of mu'amalah instead. Thus, as the increased complexity of a trade and needs, it is of course necessary to study qa'idah even more, with reference to the methods outlined in ushul fiqh. Keywords: Qawa’id al-Fiqh, Principles of Sharia Economics